Relating smart governance as a University feature to students' university perceptions - Jadrić, Mario (Array, 2021)
Following the results of recent studies on the creative use of smart technologies in urban and university settings, there is a growing number of promising research areas under smart university as an umbrella term. Starting from the differentiation between six standard "smart" dimensions in the university, the paper focuses on one smart university feature in particular – it explores the level and the relation of smart governance to the attitudes towards university management, fellow students, and Perceived External Prestige (PEP) as antecedents of university affective commitment. The paper presents multivariate analysis results based on the feedback from over 400 students. Participants were first-year students from the second biggest university in Croatia. While the effect of smart governance on the positive attitude towards university management is found to be positive and significant, the effect of the perception of university management on students' university commitment is low and not significant in the given context.